HUBUNGAN AKSES AIR MINUM DAN SANITASI PADA KELUARGA DENGAN KEJADIAN STUNTING: SCOPING REVIEW: THE RELATIONSHIP BETWEEN FAMILY ACCESS TO DRINKING WATER AND SANITATION AND THE INCIDENCE OF STUNTING: A SCOPING REVIEW - Nur'aeni, Nabyla (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2023)
Introduction: Water and soil have a role in the transmission of disease. Cases of malnourished children under five have the potential to increase due to inadequate latrine facilities and drinking water quality. This review aims to decide the relationship between family access to drinking water and sanitation and the incidence of stunting to analyze the next prevention. Methods: The approach taken is a scoping review by identifying articles in PubMed, CINAHL, and Sage from 2012-2022. The keywords used were